Pengaruh Disiplin Kerja, Kesehatan dan Keselamatan Kerja, dan Kompensasi Terhadap Produktivitas Karyawan: Studi pada PT Malindo Feedmill Tbk - Erwan Firmansyah; Sugiharti, Sugiharti (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2026)
This study aims to analyze the effect of work discipline, occupational health and safety (OHS), and compensation on employee productivity at PT Malindo Feedmill Tbk. The research employs a quantitative approach with a total of 178 employees selected through the proportionate stratified random sampling technique. Data were collected using questionnaires and analyzed through multiple linear regression with the help of SPSS 21. The results indicate that work discipline, OHS, and compensation each have a positive and significant effect on employee productivity. Furthermore, simultaneously, these three variables also have a significant influence, meaning that work discipline, proper implementation of OHS, and a fair and competitive compensation system play an important role in improving employee productivity. These findings emphasize the importance of effective human resource management implementation as a corporate strategy to enhance performance and competitiveness.